Laparoscopic repair of the caesarean section scar niche: A prospective cohort study. - Anna Abacjew-Chmylko; Dariusz G Wydra; Hanna Olszewska; Sambor Sawicki; Katarzyna Stefanska (PLoS ONE, 2025)
Objective To evaluate the effect of laparoscopic repair of the large niche on short-term and long-term outcomes, i.e., extent of scar healing (increase in scar thickness or residual myometrium (RM) and decrease in niche depth), decrease in menstrual symptoms, likelihood of conception and successful delivery. Study design A prospective observational cohort study. Methods and findings Among 333 patients referred with a niche diagnosed in transvaginal ultrasound (TVU), a group of 127 met the selection criteria for repair surgery (RM of <2.5 mm in its thinnest part in hysterosonography (HySoG) and a desire to conceive) and underwent the laparoscopic procedure (uterine cesarean scar and niche walls cold knife resection followed by resuturing of the uterine wall) between November 2015 and October 2022. The laparoscopic repair of niche increased the RM to 6.5 ± 2.6 mm in TVU and 6.1 ± 2.5 mm in HySoG. Postoperative failure, defined as incomplete scar formation with a niche and residual myometrium thickness under 2.5 mm, occurred in 8.2% of cases. Furthermore, 20.9% of scars showed residual myometrium thickness below 4 mm. Conversely, the rate of postoperative diverticulum, defined as an indentation at the site of the cesarean section scar with a depth of at least 2 mm, was 70.9%. Furthermore, indentations greater than 3 mm were found in 49.1% of cases. The surgical procedure significantly alleviated symptoms related to the niche: duration of postmenstrual spotting (P < 0.001), length of menstrual bleeding (P = 0.03), menstrual pain (P < 0.001) and menstrual flow (P = 0.02). In patients with a sustained postoperatively desire to conceive (N = 79, 62.2%) a vast majority fulfilled childbearing plans (n = 42, 53.2%), for at least once (93%). The best surgical outcomes were obtained when the procedure was performed in the follicular phase of the menstrual cycle before the peri-ovulatory time (P = 0.02) and the uterine reconstruction was employed with double-layer horizontal mattress sutures. Conclusions The conducted study demonstrated that the surgical procedure for scar repair brings benefits by reducing clinical symptoms of the defect, improving scar parameters, and achieving a high rate of successful reproductive plans.